2021
DOI: 10.1186/s40163-021-00162-9
|View full text |Cite|
|
Sign up to set email alerts
|

Offline crime bounces back to pre-COVID levels, cyber stays high: interrupted time-series analysis in Northern Ireland

Abstract: Much research has shown that the first lockdowns imposed in response to the COVID-19 pandemic were associated with changes in routine activities and, therefore, changes in crime. While several types of violent and property crime decreased immediately after the first lockdown, online crime rates increased. Nevertheless, little research has explored the relationship between multiple lockdowns and crime in the mid-term. Furthermore, few studies have analysed potentially contrasting trends in offline and online cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Several types of scams and fraud have been reported: cybercriminals are capitalizing on the anxieties and fears triggered by the pandemic, using malware, such as viruses, worms, trojan horses, ransomware, and spyware, to invade, damage, steal or delete personal data on personal computers. In addition to these types of online scams, there has been a surge in fake or inappropriate drugs and vaccines and medical equipment sold at a very high price [ 28 , 29 ]. Moreover, social isolation and decreased mobility combined with COVID-19 containment policies have inevitably increased stress levels, reducing access to social support services and increasing crime such as child abuse, domestic violence and substance abuse [ 30 , 31 , 32 , 33 ].…”
Section: The Scovid-19 Pandemic and Its Impact On Forensic Investigat...mentioning
confidence: 99%
“…Several types of scams and fraud have been reported: cybercriminals are capitalizing on the anxieties and fears triggered by the pandemic, using malware, such as viruses, worms, trojan horses, ransomware, and spyware, to invade, damage, steal or delete personal data on personal computers. In addition to these types of online scams, there has been a surge in fake or inappropriate drugs and vaccines and medical equipment sold at a very high price [ 28 , 29 ]. Moreover, social isolation and decreased mobility combined with COVID-19 containment policies have inevitably increased stress levels, reducing access to social support services and increasing crime such as child abuse, domestic violence and substance abuse [ 30 , 31 , 32 , 33 ].…”
Section: The Scovid-19 Pandemic and Its Impact On Forensic Investigat...mentioning
confidence: 99%
“…Notably, the second national lockdown imposed in England was less pronounced in reducing crime than the earlier lockdown (Farrell and Dixon 2021 ). Meanwhile, in Ireland, Buil-Gil and others ( 2021 ) observed that traditional offences like burglary, theft and violent and sexual crimes decreased during lockdowns but rebounded to pre-lockdown levels during post-lockdown (Post-L) periods. On the other hand, cybercrime in the Post-L period was higher than pre-COVID-19 levels (Buil-Gil et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The research on crime and COVID-19 in addition notes certain types of crime for which the pandemic appears to have led to more crime. This is true for domestic violence (Ivandic et al, 2020;Nesset et al, 2021;Piquero et al, 2021) and cybercrime (Buil-Gil et al, 2021b, 2021a. Increases in these crimes are expected due to changes in routine activities, as people spend more time at home, which could increase domestic violence, and online activity, which could increase cybercrime (Esiner & Nivette, 2020;Buil-Gil et al, 2021b).…”
Section: Covid-19 and Crimementioning
confidence: 99%
“…Few changes to the social environment have been so quick and dramatic as those brought about by the COVID-19 pandemic which has led to nearly 6300000 deaths across the world since 2020 (Dong et al, 2020). 1 Just two years after the pandemic struck the world, there are already dozens of studies on its impact on crime (some examples covering different parts of the world and crime types include Ashby, 2020a;Buil-Gil et al, 2021a;Campedelli et al, 2020;Ceccato et al, 2022;Estévez-Soto, 2021;J. H. Boman & Gallupe, 2020;Mohler et al, 2020;Nivette et al, 2021;Payne et al, 2021;Piquero et al, 2021).…”
Section: Introductionmentioning
confidence: 99%